Psychophysiological and psychological characteristics of underage road users - A.M. Prohorova; A.D. Gordeeva (Психология и право)
Context and relevance. The work is aimed at considering the psychophysiological and psychological foundations of adolescents' safe behavior in traffic conditions. The results of psychophysiological and psychological examination of two groups of road users are presented. Objective. To determine the psychophysiological and psychological features of adolescents forming safe behavior in the conditions of the road environment. Methods and materials. The study involved 800 road users, who were divided into 2 groups: the first group consisted of minors aged 15—17 years (400 people), the second — adults aged 18—49 years (400 people, average age 35 years). Psychophysiological and psychological examination included assessment of: the functional state of the nervous system; individual-typological properties of the nervous system; individual peculiarities of development of separate mental functions; personal characteristics. Results. The results obtained made it possible to compile, on the basis of psychophysiological and psychological research, a cumulative profile of a minor road user. Conclusions. It is shown that the compiled aggregate profile of a minor road user may indicate that it is impossible to develop a stereotype of safe behavior in traffic conditions only by teaching traffic rules. A special approach is necessary, which consists in explaining the influence of age features on behavior on the road. Such factors as age, individual-typological and individual-psychological peculiarities should be taken into account when teaching and building a system of prevention of children's road traffic injuries.